High linear energy transfer carbon-ion irradiation increases the release of the immune mediator high mobility group box 1 from human cancer cells. (27th June 2018) - Onishi, Masahiro; Okonogi, Noriyuki; Oike, Takahiro; Yoshimoto, Yuya; Sato, Hiro; Suzuki, Yoshiyuki; Kamada, Tadashi; Nakano, Takashi
Abstract: Anti-tumor immunity modulates the local effects of radiation therapy. High mobility group box 1 (HMGB1) plays a pivotal role in activating antigen-specific T-cell responses. Here, we examined the relationship between linear energy transfer (LET) and HMGB1 release. We assessed the proportions of KYSE-70, HeLa and SiHa cells surviving after carbon-ion (C-ion) beam irradiation with different LET values, using a clonogenic assay. The D10, the dose at which 10% of cells survived, was calculated using a linear–quadratic model. HMGB1 levels in the culture supernatants of C-ion beam–irradiated tumor cells were assessed by enzyme-linked immunosorbent assay. The D10 doses for 13 keV/μm of C-ion irradiation in KYSE-70, HeLa and SiHa cells were 2.8, 3.9 and 4.1 Gy, respectively, whereas those for 70 keV/μm C-ion irradiation were 1.4, 1.9 and 2.3 Gy, respectively. We found that 70 keV/μm of C-ion irradiation significantly increased HMGB1 levels in the culture supernatants of all cell lines 72 h after irradiation compared with non-irradiated controls. Furthermore, 70 keV/μm of C-ion irradiation significantly increased HMGB1 levels in the culture supernatants of all cell lines 72 h after irradiation compared with 13 keV/μm. The results suggest that HMGB1 release from several cancer cell lines increases with increased LET.